PERAN PENDIDIKAN KELUARGA TERHADAP PEMBENTUKAN KARAKTER PADA ASPEK MORAL DAN SOSIAL SISWA KELAS IX SMPN 3 MAKASSAR - Muh. Fajri Ramadan; Dalilul; Ibrahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine: 1) Describe the form of family education roles applied by parents to IX grade students at SMPN 3 Makassar 2) Analyze the role of family education in the formation of moral and social character of IX grade students at SMPN 3 Makassar 3) Analyze the role of character education in the formation of moral and social character of IX grade students at SMPN 3 Makassar. The approach used in this study is a qualitative approach with a phenomenological research type. The data collection techniques are through observation, interviews, and documentation. The data collection process in this study includes: data collection, data reduction, data presentation, and drawing conclusions. The research results show that Family Education at SMP 3 Makassar is implemented through various parenting styles, with a dominant tendency toward authoritative parenting, characterized by open communication, emotional involvement, and parental role models.